Dreading Yet Hoping: Traumatic Loss Impacted by Reference DNA Sample Collection for Families of Missing People - Wayland, Sarah; Ward, Jodie (Frontiers in Psychiatry, 2022)
The trauma of having a family member missing is commonly described as an ambiguous loss where the finality of the loss is not realized, as is experienced with a death. There is uncertainty due to the trauma of the absence and subsequent police investigation, leading to physical and emotional impacts for the aftercare of those left behind. There are 850 unidentified human remains and 2,600 long-term missing persons cases in Australia. The Australian Federal Police (AFP) National DNA Program for Unidentified and Missing Persons aims to scientifically link these cases using modern DNA techniques and databases. A DNA-led identification effort may assist to provide answers to Australian families searching for missing relatives, but may also contribute to the trauma experienced by these families. A literature review demonstrated empirical research for the development of scientific best practices for the collection of reference DNA samples for forensic purposes, but minimal evidence about the impact of reference DNA sample collection on kin when attempting to identify the deceased remains of missing people in non-mass casualty situations. The aim of this study was to develop an academically robust understanding of the unique impact of reference DNA sample collection on families of missing persons and support pathways tailored to the experience. This study involved 26 Australian families of long-term missing (ranging from 1 to 20+ years) people in Australia anonymously completing a mixed-methods online survey about their experiences of providing reference DNA samples to aid missing persons investigations. Respondents were representative of a range of ages, genders and relationships to the missing individual. The thematic analysis of the survey results identified the provision of a reference DNA sample: (1) resembles an overt act of hope as families perceive their sample assists the investigation, whilst also being traumatic, triggered by the prospect of scientifically matching their missing family member to a set of unknown human remains; (2) can cause immediate interpersonal impacts and ongoing impacts to families' wellbeing; and (3) can be improved by considering the environment where the sample is collected, professionalism of the police officer collecting the sample, timeliness of the provision of the sample, level of support provided during and after sample collection, and effective communication of forensic procedures and processes as they relate to the missing persons investigation. The study concludes that the complexity associated with provision of family reference samples requires the development and implementation of best practice guidelines, including psycho-education strategies to be used by practitioners to minimize the vicarious trauma for relatives already traumatized by the loss of their missing family member. These guidelines would support the objectives of the AFP Program and benefit all routine missing persons investigations.